2007
DOI: 10.1371/journal.pone.0000371
|View full text |Cite
|
Sign up to set email alerts
|

Increased Neural Activity of a Mushroom Body Neuron Subtype in the Brains of Forager Honeybees

Abstract: Honeybees organize a sophisticated society, and the workers transmit information about the location of food sources using a symbolic dance, known as ‘dance communication’. Recent studies indicate that workers integrate sensory information during foraging flight for dance communication. The neural mechanisms that account for this remarkable ability are, however, unknown. In the present study, we established a novel method to visualize neural activity in the honeybee brain using a novel immediate early gene, kak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
124
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(137 citation statements)
references
References 47 publications
10
124
0
Order By: Relevance
“…Results from GO analyses highlight the function of the mushroom bodies in learning and memory, with enrichment in categories such as transcriptional regulation and ion channel activity, among others. These results are consistent with known roles for the mushroom bodies in the regulation of rhythmic behavior, learning and memory [28,29,33,56,57]. In addition, our results nicely correspond with earlier in situ hybridization data and immuno-staining data for genes like Inositol tris-phosphate receptor, CAMKII and PKA that were also shown to be highly expressed in mushroom bodies [48,50,54].…”
Section: Discussionsupporting
confidence: 92%
“…Results from GO analyses highlight the function of the mushroom bodies in learning and memory, with enrichment in categories such as transcriptional regulation and ion channel activity, among others. These results are consistent with known roles for the mushroom bodies in the regulation of rhythmic behavior, learning and memory [28,29,33,56,57]. In addition, our results nicely correspond with earlier in situ hybridization data and immuno-staining data for genes like Inositol tris-phosphate receptor, CAMKII and PKA that were also shown to be highly expressed in mushroom bodies [48,50,54].…”
Section: Discussionsupporting
confidence: 92%
“…In honey bees, mushroom body neuropil undergoes age-related expansion roughly coincident with orientation flights in both workers and reproductives (Fahrbach et al, 1995;Brandon and Coss, 1982;Withers et al, 1993;Fahrbach et al, 1997), and as mentioned above, one study found rapid remodeling of dendritic spines in the mushroom bodies after an orientation flight (Brandon and Coss, 1982). In addition, Kiya et al (Kiya et al, 2007) found evidence of neuronal activation in the mushroom bodies of reorienting foragers. Drosophila have minimal mushroom bodies that receive olfactory input almost exclusively (Heisenberg, 2003), while those of honey bees comprise a substantial portion of total brain volume and receive significant visual and olfactory input.…”
Section: Discussionmentioning
confidence: 85%
“…One such species is the European honeybee Apis mellifera L. In addition to being an important pollinator in agriculture, the honeybee is a model animal for studies of the molecular and neural bases underlying social behaviors (Kamikouchi et al, 1998;Rybak et al, 1998;Menzel and Giurfa, 2001;Takeuchi et al, 2001Takeuchi et al, , 2002Kucharski et al, 2002;Kiya et al, 2007;Sen Sarma et al, 2009;Kaneko et al, 2013). The honeybee is a social insect and colony members exhibit various complex social behaviors.…”
Section: Introductionmentioning
confidence: 99%